2013
DOI: 10.1063/1.4798429
|View full text |Cite
|
Sign up to set email alerts
|

Constructal law of design and evolution: Physics, biology, technology, and society

Abstract: This is a review of the theoretical and applied progress made based on the Constructal law of design and evolution in nature, with emphasis on the last decade. The Constructal law is the law of physics that accounts for the natural tendency of all flow systems (animate and inanimate) to change into configurations that offer progressively greater flow access over time. The progress made with the Constructal law covers the broadest range of science, from heat and fluid flow and geophysics, to animal design, tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
190
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 311 publications
(196 citation statements)
references
References 197 publications
(193 reference statements)
2
190
0
4
Order By: Relevance
“…In particular, Bejan [37,38] has argued that constructal law governs the natural evolution and motion efficiency. Dumas [39,40] and Trancossi [41,42] have defined a technical design methodology for transport vehicle obtaining in the case of airships an effective optimization up to energy complete self-sufficiency by photovoltaic energy.…”
Section: Optimization Of Ground Vehiclesmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, Bejan [37,38] has argued that constructal law governs the natural evolution and motion efficiency. Dumas [39,40] and Trancossi [41,42] have defined a technical design methodology for transport vehicle obtaining in the case of airships an effective optimization up to energy complete self-sufficiency by photovoltaic energy.…”
Section: Optimization Of Ground Vehiclesmentioning
confidence: 99%
“…Bejan [34][35][36][37][38] has defined constructal theory, which is an effective method to understand the elementary logic of natural evolution and to allow design of more efficient …”
Section: Optimization Of Ground Vehiclesmentioning
confidence: 99%
“…In [16], it is confirmed that the type of motion occurring while a fluid flows in a duct chooses is the one that assures maximum entropy generation (or minimum, depending on the constraints). Entropy is used for describing different phenomena involving both biological and inanimate systems, such as animal locomotion, vegetation, organ size, water basins and social organization [18,19]. As regards the discrepancy between the concepts of maximum and minimum entropy generation, in [20,21] it has been established that maximum entropy production principle can be considered as a direct consequence of minimum entropy generation.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 The evolutionary designs that emerge naturally are tree-shaped when the tendency of the flow is to flow more easily between areas (or volumes) and discrete points. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] An important contemporary application of the tree-shaped design is in the energy storage systems.…”
Section: Introductionmentioning
confidence: 99%